A strategic analysis of Diwannie layer cakes / Suudi Arof...[et.al] - Arof, Suudi; Jahet, Dihem (2015)
The purpose of this study is to conduct a strategic analysis on Diwannie Layer Cakes, a product of Wannie Enterprise, a producer of the renowned Sarawak layer cake since 30 years ago. The Sarawak layer cake is very famous and has become a must-buy product for tourists visiting the state, or their visit is considered incomplete if they return home without buying the Sarawak layer cake.